KOMITE MADRASAH DALAM PENGELOLAAN SARANA DAN PRASARANA DI MADRASAH IBTIDAIYAH MABDAUL ULUM ROWOSARI - Hardiana, Tariza; Sholihah, Imro`atus (LP2M STAI AL-UTSMANI BONDOWOSO, 2024)
This journal aims to describe the role of madrasah committees in the procurement, distribution and maintenance of facilities and infrastructure.This research uses a qualitative research approach with a descriptive case study type. The results of this research are 1) the role of the madrasah committee in providing facilities and infrastructure, its role has been carried out well. Such as giving consideration in the form of suggestions, input and participating in deciding what facilities will be provided. Providing support in the form of fundraising from the community. As controller, supervises madrasa activities. As a mediator or liaison, collaborate with the community so that they can contribute to the procurement process carried out by the madrasah, convey aspirations, ideas and demands submitted by the community to the madrasah. 2) the role of the committee in the distribution of facilities and infrastructure, namely: a. Preparing the allocation of goods, as a consideration provider by providing input and suggestions when determining the recipient according to the goods to be distributed. B. Delivery of goods, providing support in the form of personnel assistance by participating in the delivery process. C. Delivery of goods, as controller supervises the process of handing over goods according to procedures, and checks the completeness of documents supporting distribution. 3) the role of the committee in maintaining facilities and infrastructure, as a mediator (liaison). The committee invites students and the community to take part in caring for, looking after and maintaining the facilities at the madrasah, so that the facilities and infrastructure can last longer and are not easily damaged